Carrying Capacity Assessment of the Aik Nyet Natural Tourism Area in Buwun Sejati Village, West Lombok Regency - Indrayana, Rifaldy; Ichsan, Andi Chairil; Wahyuningsih, Endah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The increase in the number of tourists in 2023, based on data from KPH Rinjani Barat, is 36,788 visits per year. Large and continuous tourist visits to a certain area can have negative impacts on the environment and the visitors themselves. This study aims to assess the carrying capacity of the Aik Nyet natural tourist area to ensure it can support ongoing visitor activities. The tools used in this study include writing materials, GPS, questionnaires, raffia ropes, and tally sheets. The materials used in this research include area maps, bio-physical conditions, visitor information, and vegetation data in the Aik Nyet tourist area. Both qualitative and quantitative methods were employed in this study. The findings show that the physical carrying capacity (PCC) is 25,232 people. The real carrying capacity (RCC) can accommodate 24,663 people, and the effective carrying capacity (ECC) can support 9,865 people. Monitoring of the water quality in the area is recommended.